Tissue Perfusion Changes after Direct and Indirect Angiosome Revascularization in Critical Limb Ischemia - Baltrūnas, Tomas; Račytė, Austėja; Pikturnaitė, Gabija; Ašakienė, Ingrida; Labunskas, Vaidas; Kalvaitis, Evaldas; Ručinskas, Kęstutis (Lietuvos chirurgija, 2022)
Background. Blood flow restore in critical limb ischemia according to angiosomes is becoming very popular. This method allows to restore blood flow precisely to the artery supplying the ischemic zone, based on the angiosome concept. However, angiosome revascularization is not a gold standard because of the lack of evidence supporting this approach. The aim of this study was to compare tissue oxygenation changes in ischemic zone during endovascular revascularization procedure either following angiosome concept or performing indirect revascularization. Methods. A prospective observational study was performed. Patients with critical limb ischemia and tissue loss due to chronic total occlusion of below the knee arteries were included. Endovascular revascularization was performed in all cases. Tissue oxygen saturation was observed intraoperatively using near-infrared spectroscopy. Tissue oxygenation changes near the ischemic wound were compared between direct and indirect revascularization groups. Results. This clinical trial included 30 patients with critical limb ischemia (Rutherford 5) and occluded below the knee arteries intended to treat. In 15 patients the procedure was performed according to angiosome, while the other half underwent indirect revascularization. Tissue oxygenation near the wound was monitored during the intervention. Greater oxygen saturation increase was observed in the group with direct revascularization (29% and 23% accordingly), however the difference between groups was not statistically significant (t-test for independent group, p = 0,544). Conclusions. The increase in tissue oxygen saturation differed very slightly in direct and indirect revascularization groups and the difference was statistically insignificant.
Keywords: critical limb ischemia; angiosome; near-infrared spectroscopy; endovascular revascularization